Managerial reporting, overoptimism, and litigation risk - Laux, Volker; Stocken, Phillip C. (Journal of Accounting and Economics, 2012)
We examine how the threat of litigation affects an entrepreneur's reporting behavior when the entrepreneur (i) can misrepresent his privately observed information, (ii) pays legal damages out of his own pocket, and (iii) is optimistic about the firm's prospects relative to investors. We find higher expected legal penalties imposed on the culpable entrepreneur do not always cause the entrepreneur to be more cautious but instead can increase misreporting. We highlight how this relation depends crucially on the extent of entrepreneurial overoptimism, legal frictions, and the internal control environment.